Exploring the genetic pathogenicity of aortic dissection from 72 Han Chinese individuals using next‐generation sequencing. Issue 5 (16th March 2020) - Pan, Meichen; Chen, Shu; Wang, Haihao; Wu, Shifan; Ding, Zijiao; Wang, Yuning; Li, Lianjie; Li, Zehao; Liu, Qian
Abstract: Aortic dissection (AD) is a heterogeneous genetic disease with high morbidity and mortality. Although many genes predispose patients to AD, the pathogenic spectrum remains incomplete. This study aims to (a) investigate whether genotype differences exist between Stanford A and B AD individuals, and (b) broaden the pathogenic genetic spectrum of AD and reported novel variants of AD‐associated genes. The DNA of 72 unrelated Han Chinese individuals with AD was tested by whole‐exome sequencing. Of 142 AD‐associated genes, 10 pathogenic variants, and 48 likely pathogenic variants in 36 genes were identified among 39 cases. The diagnostic yield was 54.2%. Of the 58 positive variants, 27 were novel. FBN1 was the most frequently positive gene in both Stanford A and Stanford B. Twenty‐seven positive variants from 18 COL family genes were distributed in 36.8% of Stanford A and 6.7% of Stanford B cases. We emphasize that positive variants of COL family genes show distribution predominance and strong pathogenicity in Stanford A, while positive variants of smooth muscle cell pathway genes present distribution advantages mainly in Stanford B cases. Our findings provide a new perspective for both the pathogenic mechanism and the treatment of AD. Abstract : Detailed distribution of 58 positive variants in 72 Han individuals.